AW09 Tail Rotor System Control Authority Assessment - Bölk, S.; Masi, A.; Scorcelletti, F. (My University, 2023)
The tail rotor of a helicopter plays a crucial role in maintaining stability and control during flight. Therefore, it is essential to meet several performance and controllability requirements to ensure safe and efficient operation. One of these requirements is providing sufficient yaw control authority to enable the pilot to maneuver the helicopter effectively. However, specific challenges arise when dealing with a ducted tail rotor, such as the one installed in the AW09 helicopter—an innovative multi-role single-engine aircraft currently under development at Kopter Group AG. The current approach to modeling the yaw control authority involves calculating the tail rotor thrust using a commercial tool in a full aircraft model. Subsequently, the simulation of the tail rotor blade pitch and the corresponding pedal control demand is performed using an in-house developed code. The decision to develop a dedicated code for the tail rotor was made to ensure maximum modeling flexibility and tuning capabilities, enabling accurate replication of the behavior of the AW09 ducted rotor. In this paper, we present the methodology that combines a dedicated rotor analysis tool with the commercially available software, FLIGHTLAB, to verify the AW09 tail rotor system against a series of helicopter certification and operational requirements. Due to data confidentiality, the figures in the results section are presented without scales.
Keywords: Flight Mechanics